Study porous pressure and cracking pressure in well NS 13, Southern Iraq - Mahdi.A.Menshed (University of Thi-Qar Journal of Science, 2021)
In this study we examined the behavior porous pressure and cracking pressure in well NS 13 as it is the only well which the two cavity logs, second and third are available. We used interactive petrophysics 3-5 program prepared by Schlumberger company, for calculate pore pressure and cracking pressure by feeding the program with the sonic log readings which are IAS file format, and also the pressure was calculated using the drilling operations for the purpose of comparing and discussing the results to arrive at the best solution to avoid problems that occurred during drilling the previous wells from the loss of drilling fluids, and reservoir flow, and bad cement production lining , and give suggestions, which contribute to solving the problem.